Оптико-тепловий метод контролю газових потоків - Мощенко, І. О.; Єгоров, А. Б. (ХНУРЭ, 2005)
The physical and mathematical description of the precision contactless method of natural gas charge measurement developed by the author for pipelines of the big diameters is offered. The control of gas streams is based on optical principles. The known optical method is advanced by adding in the structural scheme of the device, realizing the given method, an external local source of heating that allows increasing sensitivity of the method. Нафтогазова промисловість України, як окрема галузь паливно-енергетичного напрямку економіки держави, сьогодні одна з найперспективніших й найбільш інтелектуально насичених у народногосподарському комплексі. Забезпечення високоточного обліку й ощадливого використання природного газу є сьогодні найважливішим науковим і практичним завданням науки і техніки України.
Keywords: метрологія; Нафтогазова промисловість